Students’ Perceptions of an English Club Activities in Enhancing Speaking Confidence among Junior High School - Nida Khasanatu Zain; Sri Wahyuni (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
Speaking confidence is an important factor in students’ participation in English speaking activities, yet previous English Club studies have mainly focused on students’ learning outcomes rather than how speaking confidence develops through their participation. This study aims to explore junior high school students’ perceptions of English Club activities and how these activities contribute to their speaking confidence. Employing a qualitative descriptive design, this study involved six students who actively participated in an English Club at SMP Negeri 25 Semarang. Data were collected through semi-structured interviews and non-participant observation and analyzed using Braun and Clarke’s (2006) six-phase thematic analysis. The findings revealed three themes: (1) the English Club as an enjoyable and supportive learning environment, (2) perceived growth in speaking confidence through speaking experiences, and (3) different activities addressing different speaking needs. Students perceived that repeated speaking practice, observation of teachers and peers, feedback and encouragement, and reduced nervousness contributed to their speaking confidence. These findings were interpreted through Bandura’s (1997) four sources of self-efficacy: mastery experiences, vicarious experiences, verbal persuasion, and physiological and affective states. The novelty of this study lies in explaining how students’ experiences in different English Club activities are perceived to contribute to speaking confidence through the sources of self-efficacy. The study highlights the importance of providing varied speaking activities and a supportive environment to foster students’ speaking confidence.